Implicit force and position control to improve drilling quality in CFRP flexible robotic machining - Lee, Jinho; Hong, Taehwa; Seo, Chang Hoon; Jeon, Yong Ho; Lee, Moon Gu; Kim, Hyo Young (Journal of Manufacturing Processes, 2021)
Flexible machining systems are being widely applied in the aircraft and automotive industries to reduce costs and increase productivity. The workpieces for the corresponding applications are bigger and more varied than those for conventional applications. These workpieces can be made of carbon fiber reinforced plastic (CFRP) because it provides a high strength-to-weight ratio. Nevertheless, CFRP has poor machinability owing to its brittleness. To achieve flexible machining, industrial robots are being increasingly adopted, especially for drilling. However, they cannot meet industrial requirements such as machining precision, cost, and productivity. This is because industrial robots have a considerably lower stiffness than conventional computer numerical control machines given their structure consisting of serial links. Consequently, tasks such as drilling using industrial robots may present production defects. Drilling defects generally appear as burrs in the hole entrance and deviations of the desired hole center. In this study, the patterns and causes of such defects during robotic drilling were analyzed, and it was determined that the main defect was caused by the deviation of the tool tip due to the low robot stiffness. The defect was then corrected using implicit force and position control. Experimental results showed that when the defect was corrected, the maximum hole diameter error decreased by 16.68% when compared with a scenario in which no compensation for the defect was made. In addition, the maximum error decreased by 10.83% when compared with drilling that was guided by a pilot hole.
Keywords: Automotives; Carbon-fibre reinforced plastics; Drilling quality; Flexible robotics; High-strength; Machining systems; Plastic flexible; Reduce costs; Robotic machining; Workpiece; CFRP; Control; Drilling; Robotic machining; Robotics